Zarządzanie informacją w profesjonalnym klubie sportowym - Barylski, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Together with the development of professional sport, it is possible to observe the changes in the management process of a sports club product, connected with the application of multimedia information techniques. The concept of effective information management has been relativized to the situation of a sports club existing in the circumstances of a market game. In this case, it has been assumed that the efficiency of sports product management can be increased with more rational and wider application of multimedia information techniques. The paper fully describes the techniques presently used by clubs and sports associations, and the solutions possible to follow. The novelty of the presented concept means the presentation of full application of information techniques in order to improve the management of a sports product. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 20-28